Acute Bismuth Intoxication: Acute Renal Failure, Tonsillar Ulceration and Posterior Reversible Encephalopathy Syndrome. Issue 2 (March 2015) - Akinci, E; Köylü, R; Yortanli, M; Gümüş, H; Köylü, Ö; Altintepe, L; Cander, B
Consumption and production of bismuth compounds are increasing, however, little information on the toxic effects and effective methods in removal of bismuth compounds are available. Although bismuth intoxication is currently rare, a careful evaluation should be carried out for possible exposure. We reported a16-year-old female who developed acute kidney failure, tonsillar ulceration and posterior reversible encephalopathy syndrome after an ingestion of 19 grams of bismuth subcitrate for suicidal attempt. (Hong Kong j.emerg.med. 2015;22:121-125)